Análise da gestão de estoques em um supermercado regional - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Good inventory control of a company is an essential activity to ensure its competitiveness. This work aims to clarify the importance of good inventory management by adopting the necessary tools to achieve management efficiency, thus being able to differentiate from competitors, improving quality, reducing time, reducing costs and consequently multiplying profits by acquiring a competitive advantage. The study is carried out in a supermarket chain in the southern region of Rio Grande do Sul, where the qualitative method is used, where the data collection is done through semi-structured interviews with the employees of the company's inventory sector, with the objective of analyzing the inventory management system adopted by the network to see how inventory management is given in the organization mainly in relation to its efficiency. The research was successfully applied reaching the proposed objectives, and with the results of the study it was concluded that the company still has a stock management system quite flawed which does not allow to be considered efficient.
Analysis of stock management in a regional supermarket
Keywords: Controle de estoque; Logística; Supermercados; Administração; Inventory control; Logistics; Management; CNPQ::CIENCIAS SOCIAIS APLICADAS